Modeling of the institutional system of enterpreneurship promotion: the case of Lithuania - Pauliukevičius, Gediminas; Skusevičienė, Dorota (Business, Management and Economics Engineering, 2013)
The purpose of the article is to review the institutional system of entrepreneurship promotion that exists in Lithuania and to offer guidelines to improve it. The research results show that the unified institutional system of entrepreneurship promotion in Lithuania does not present: responsible institutions coordinate single measures and their implementation, but do not follow long-term general strategy. According to research findings, in order to improve the entrepreneurship promotion system of Lithuania there is a need to create the main institutional system out of responsable ministries (the Ministry of Education and Science, the Ministry of Economy, the Ministry of Agriculture, the Ministry of Social Security and Labour) and define the boundaries of their responsibilities.